Seismic hazard assessment for Adria - D Slejko; R Camassi; Cecic,I.; D Herak; M Herak; S Kociu; V. Kouskouna; J Lapajne; Makropoulos, K.; Meletti, C.; B Muço; Papaioannou, C.; et al. (Annali di Geofisica, 1999)
The Adriatic region was chosen as one of the test areas in the GSHAP program and, consequently, its seismic hazard was computed. The standard hazard map chosen by GSHAP represents PGA with a 475-year return period. Some other parameters, as the spectral acceleration and the uniform hazard response spectra for the main Adriatic towns, have been computed for a better representation of the regional hazard. The most hazardous area remains identified in the Cephalonia zone, where strong earthquakes frequently occur. The Southern Apennines are characterised by a slightly lower hazard, while the Adriatic Sea itself, the Po plain and the Apulian peninsula are almost aseismic.